2018
DOI: 10.1186/s12931-018-0945-2
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial cells exposed to wildfire smoke extract exhibit dysregulated autophagy and barrier dysfunction consistent with COPD

Abstract: BackgroundIndividuals with respiratory disease are being increasingly exposed to wildfire smoke as populations encroach further into forested regions and climate change continues to bring higher temperatures with lower rainfall. Frequent exposures have significant potential to accelerate conditions such as chronic obstructive pulmonary disease (COPD) which is characterised by an exaggerated inflammatory response to environmental stimuli. Here we employ models of human airway epithelium exposed to wildfire smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
1
35
1
Order By: Relevance
“…In addition, an increase in inflammatory gene expression was observed in cells exposed to wood tar extract ( Table 1 and Additional file 1: Figure S6). Some in vitro studies on exposure to water-soluble extracts from collected biomass burning particles have also indicated that exposure induces onset of an inflammatory response similar to that observed in our study [4,28,43,44], while other studies have shown only a minor inflammatory response following exposure to biomass burning extracts [42,45,46]. The combined results from this study suggested that the inflammatory response was increased in both the in vivo and in vitro exposures.…”
Section: Inflammatory Responses After Exposure To Wood Tar Aerosolssupporting
confidence: 87%
“…In addition, an increase in inflammatory gene expression was observed in cells exposed to wood tar extract ( Table 1 and Additional file 1: Figure S6). Some in vitro studies on exposure to water-soluble extracts from collected biomass burning particles have also indicated that exposure induces onset of an inflammatory response similar to that observed in our study [4,28,43,44], while other studies have shown only a minor inflammatory response following exposure to biomass burning extracts [42,45,46]. The combined results from this study suggested that the inflammatory response was increased in both the in vivo and in vitro exposures.…”
Section: Inflammatory Responses After Exposure To Wood Tar Aerosolssupporting
confidence: 87%
“…Therefore, the present study showing an increase in obstructive pathology based on spirometry results suggests a model of increased acute inflammation and activation of the innate immune system from wildfire smoke that results in tissue remodeling and decreased lung function ( Figure 6). firefighters and in vitro studies reported increased IL-6, a contributor to inflammatory lung pathology [33,34], in response to wildfire or wildfire smoke extract, respectively [35,36]. The firefighters were assessed in the acute phase and found increased serum levels of IL-6, IL-8 and decreased IL-10, while the lung epithelial cultures presented with increased IL-6 production in addition to other markers of COPD including dysfunction of tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The ILC2 are important sources of IL-13 (35) and have been linked to asthma, an obstructive lung pathology. Additionally, studies in both re ghters and in vitro studies reported increased IL-6, a contributor to in ammatory lung pathology (36,37), in response to wild re or wild re smoke extract, respectively (38,39). The re ghters were assessed in the acute phase and found increased serum levels of IL-6, IL-8 and decreased IL-10, while the lung epithelial cultures presented with increased IL-6 production in addition to other markers of COPD including dysfunction of tight junctions.…”
Section: Discussionmentioning
confidence: 99%